Power of Scent Marketing to Influence Consumer Behavior - Rathee, Rupa; Rajain, Pallavi (Indian Journal of Marketing, 2018)
The smell of food cooking in the kitchen can invoke numerous thoughts of good experiences while enjoying that food. This same effect is used by scent marketers to emotionally connect with customers in case of other products besides food. Hence, the current paper attempted to study previous literature relating to the use of scent marketing as well as cited certain instances where this technique is being applied. In the present study, previous articles and papers were reviewed and analyzed to get a grip of what is the present knowledge in this area and what more can be done in the future. It was found that for the past two decades, marketers have been trying to find the relationship between the use of different kinds of scents and their effects in varied environments. It was seen that when an ambient scent was congruent with the environment, it had a significantly positive impact on the behavior of the customers present. Similarly, the approach-avoidance behavior of customers was influenced by manipulating their moods with the use of scents. Thus, it can be said that the products are no longer judged only by their inherent quality, it is also the quality of the environment in which they are purchased that appeals to the customers. The study is novel in its approach of viewing behavioral responses to scent and use of technology in scenting the environment. The study also provided certain propositions which can be tested in future research studies.